Analysis of Risk Severity of Nomophobia in Regular Basic Education Students in the Region of Puno, Peru - Yanqui, Fidel Ticona; Cariapaza, Luz Maria Meneses; Arapa, Victoria Delfina Quispe; Maquera, Yuselino Maquera (Journal of Ecohumanism, 2024)
This research work analyzes the severity of the risks of nomophobia in students of Regular Basic Education (EBR) in the Puno region, Peru. A descriptive observational approach was used to evaluate a sample of students from first to fifth year of secondary school, using the Nomophobia Questionnaire (NMP-Q). The main indicators evaluated included the frequency of mobile phone use, symptoms of anxiety or stress, impact on academic performance, social interactions, physical health problems, sleep quality and self-control capacity. The results indicated that 65% of students in state schools access the Internet only through their mobile phones, while 56% of students in private schools also use computers. In addition, 52 % of respondents use the Internet between 1 and 2 hours a day, while 25% use it between 3 and 4 hours. Anxiety symptoms were reported by 42% of students, while 45% reported a negative impact on their academic performance. 35% of students reported that mobile phone use affects their sleep quality, and 30% mentioned difficulties with self-control. These findings suggest the need for interventions to mitigate the effects of nomophobia in students.